Cardiac resynchronization therapy in patients with true left bundle branch block : a systematic review and meta-analysis. (4th February 2022) - Cheng, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background Cardiac resynchronization therapy has been shown to improve clinical outcomes of heart failure. Still, about 30% of the patients had no response to CRT. A stricter LBBB criteria emphasizing notched or slurred R waves was newly proposed by Strauss to select patients for CRT. Purpose To evaluate whether true left bundle branch block defined by Strauss criteria predicts a better clinical and instrumental response to CRT. Methods A systematic review and meta-analysis was performed. Cohort studies including CRT patients with true left bundle branch block (LBBB) and non-true LBBB patients were identified. Non-true LBBB patients were defined as the patients who have conventional LBBB QRS morphology but not fulfilling Strauss criteria according to the ECG characteristic. Outcomes included death, heart failure(HF) hospitalization, CRT nonresponse, changes in QRS duration and left ventricular ejection fraction(LVEF). Results Eight studies characterizing 1697 patients were identified. Pooled analysis of random effrct model demonstrated that true LBBB patients, as compared to non-true LBBB patients, had noticeable reduction in HF hospitalization or mortality (HR 0.49, 95%CI 0.40, 0.59; p < 0.001), mortality alone (HR 0.55, 95%CI 0.46, 0.66; p < 0.001), and HF hospitalization alone (HR 0.45, 95%CI 0.22, 0.93; p = 0.031). For other CRT response parameters, true LBBB patients had a significantly greater improvement of LVEF (SMD 7.30, 95%CI 0.57, 14.03; p < 0.001) .And the pooled value of the reduction in QRS duration was higher in the true LBBB patients (WMD -11.56, 95% CI -25.58, 2.45, P < 0.001). Overall, there were more responders in the true LBBB patients than non-true LBBB patients (OR 8.16, 95% CI 1.64, 40.46, P < 0.001). Conclusions True left bundle branch block patients benefits more than non-true LBBB patients. Therefore, Strauss criteria of true LBBB is strong predictor of lower mortality, HF hospitalization and better response to CRT. (PROSPERO number : CRD42021242318)